Religiosity, Trust, and Literacy Drive Islamic Finance Adoption - Muhammad Iqbal Asyari Lubis; Tuti Anggraini; Aqwa Naser Daulay (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Despite Indonesia's Muslim-majority population, the market share of Islamic financial products remains low. Specific Background: Islamic financial literacy, trust in financial institutions, and personal religiosity have been identified as key determinants in financial decision-making, yet empirical studies show inconsistent findings. Knowledge Gap: Previous research has not adequately assessed these three factors simultaneously, particularly within a student population that receives Islamic education. Aims: This study aims to examine how religiosity, trust, and sharia financial literacy affect students’ interest in using Islamic financial products. Results: Based on a survey of 100 purposively sampled students at UIN North Sumatra, multiple linear regression analysis revealed that all three variables — religiosity (β = 0.345), trust (β = 0.445), and sharia financial literacy (β = 0.236) — have a positive and significant relationship with interest in using Islamic financial products, explaining 74.2% of the variance. Novelty: This study is one of the first to simultaneously analyze these predictors among students of an Islamic university, providing insights into the behavioral intentions of a strategically important demographic. Implications: The findings underscore the need for collaborative efforts between Islamic financial institutions and universities to foster literacy, trust, and religious alignment with financial behavior among youth.Highlights: Trust is the strongest predictor of product interest among students. Sharia financial literacy significantly correlates with usage interest. The model explains 74.2% of the variation in interest behavior. Keywords: religiosity, trust, Islamic financial literacy, student behavior, Islamic banking